OPTIMALISASI SUPERVISI AKADEMIK UNTUK MENINGKATKAN KUALITAS LAYANAN PENDIDIKAN - Husni, Husni Hamdani; Aan, Aan Komariah; Dedy, Dedy Achmad Kurniady (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Teachers still need to have the ability to understand the subject matter that will be delivered to students as a teacher's duty and responsibility, including understanding the content of the material and learning objectives, thus hampering the education service process. This research aims to analyze the effect of implementing academic supervision on improving the quality of educational services in the elementary school environment. This research uses a quantitative approach using probability sampling techniques, and sampling is carried out using simple random sampling. The subjects of this research were elementary school teachers. The school categories selected were public and private junior high schools. The instruments used in this research were interview guidelines, questionnaires, and observations. Data collection was developed as a questionnaire instrument to test the correctness and suitability of indicators for academic supervision and educational services. Then, see a picture of the average trend of each variable. The research results show that the implementation of academic supervision and educational services has been carried out very well, with the overall Weight Mean Score (WMS) calculation results having very high dimensions for the supervision variable. The academic supervision program also significantly improves the quality of education services.